2010
DOI: 10.1155/2010/517594
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Mediators of Toxic Shock and Their Correlation to Lethality

Abstract: Bacterial exotoxins and endotoxins both stimulate proinflammatory mediators but the contribution of each individual toxin in the release of mediators causing lethal shock is incompletely understood. This study examines the cytokine response and lethality of mice exposed to varying doses of staphylococcal enterotoxin B (SEB) or lipopolysaccharide (LPS) and their combinations. In vivo, SEB alone induced moderate levels of IL-2 and MCP-1 and all mice survived even with a high dose of SEB (100 μg/mouse). LPS (80 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 26 publications
2
57
0
1
Order By: Relevance
“…The canonical role of IL-2 is to promote T cell expansion (38,39). This suggests that IL-2 induction in vivo by SEB has peaked before day 3, and indeed Krakauer et al (28) demonstrated a significant increase in IL-2 expression up to 24 h post exposure, and this may have been missed in sera collected on day 3. Previous studies have demonstrated that IL-1b is predominately produced by monocytes after superantigen exposure (40).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The canonical role of IL-2 is to promote T cell expansion (38,39). This suggests that IL-2 induction in vivo by SEB has peaked before day 3, and indeed Krakauer et al (28) demonstrated a significant increase in IL-2 expression up to 24 h post exposure, and this may have been missed in sera collected on day 3. Previous studies have demonstrated that IL-1b is predominately produced by monocytes after superantigen exposure (40).…”
Section: Discussionmentioning
confidence: 98%
“…Other murine models require potentiating agents such as LPS, actinomycin D, or D-galactosamine to be given in conjunction with SEB because mice are less sensitive to SEB than humans (13,23). These potentiating agents may mask the efficacy of otherwise effective medical countermeasures (28). D-Galactosamine has been shown to cause liver damage, and LPS is known to induce inflammatory pathways through TLR4 rather than through the APC/T cell immunological synapse, as occurs after exposure of SEB (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a proinflammatory cytokine with diverse biological activities which can be induced in many cell types, including peripheral blood monocytes, by stimuli such as endotoxin and IL-1β (30). Conceivably, IL-6 could have synergized with TNF-α and IL-1β to induce mortality (46). The lack of mortality in TNF-α knockout mice is in agreement with this view.…”
Section: Discussionmentioning
confidence: 99%
“…Such high damage at a low LPS dose, although not seen under nominal conditions, may indicate weaker regulatory structures leading to uncontrolled inflammation. Some possible experimental scenarios where lower than normal lethal dose could be harmful include aged mice (Kovacs et al, 2009; Plackett et al, 2004) and mice subjected to multiple lethal challenges (Krakauer et al, 2010). Many studies also indicate the possibility of other host-specific factors as equally important in driving a self-resolving vs. a self-maintaining response of inflammation (Clermont et al, 2004; Daun et al, 2008b; Foteinou et al, 2009b; Nathan, 2002).…”
Section: Discussionmentioning
confidence: 99%